The current status of the critically endangered Caerulean Paradise-flycatcher Eutrichomyias rowleyi on Sangihe, North Sulawesi - Bashari, Hanom; Lionata, Hilda; Fauzan, Panji Ahmad (KUKILA, 2016)
The Caerulean Paradise-flycatcher Eutrichomyias rowleyi is one of eight endemic birds on Sangihe. Its remaining population is only known from primary forest in valleys between 390-674 m above sea level on Mount Sahendaruman. IUCN has categorized the species as Critically Endangered. The rediscovery of 19 individuals in 1998 sparked new hope of their continued survival. We conducted population surveys in 15 valleys on Mount Sahendaruman during May–June 2014. Our estimated population size of 34–150 individuals suggests that there has not been any significant increase. The small area of remaining primary forest on the mountain (519 ha) is assumed to be the main limiting factor on population growth. The conversion of forest into plantation remains the main threat to this species, along side changes of forest floristic composition, with introduced plants pushing into its habitat. Participatory agreements on area management that were formulated in 2005, including zoning system, should be revitalized and replicated forother villages to conserve the species.